The Mangyans of Mindoro - Romualdez, Philip (Englewood Cliffs, N.J : Prentice-Hall, International, Inc., 1978)
A teenager's narrative and photographs depict the life of a primitive tribe living in the mountains of Mindoro
Keywords: Mangyans (Philippine People) -- Juvenile literature; Mangyans (Philippine People) -- Children's writings